English Language Teachers’ Experiences of Using ICT in ELT - Saud, Dammar Singh; Laudari, Suman (Journal of NELTA, 2023)
While technologies have penetrated all regions and states in Nepal – a developing country with challenging terrains – teacher educators’ practices, especially those in remote areas, are still unexplored. Integrating innovative technologies into English language education, in this context, has become essential as their aff ordances help to enhance teaching and learning. This hermeneutic phenomenological research paper, hence, explores the perspectives and experiences of using ICT in English language teaching by four English language teacher educators in Darchula, a remote district located in the Sudurpaschim Province of Nepal. Semi-structured interviews were conducted and analysed thematically. The fi ndings indicate positive attitudes among English language teacher educators towards incorporating ICT in ELT, as it enhances learning and teaching experiences, fosters student engagement, improves access to learning resources, and establishes dynamic and interactive learning environments. This study emphasises the importance of effectively integrating ICT in English language teaching while addressing technical obstacles and striking a balance between online resources to maximise benefi ts and mitigate drawbacks.